Upaya Mengembangkan Kemampuan Guru Terhadap Literasi Digital Di TK Negeri Pembina Kalianda - Anisa Nurul Aini; Muhamad Hanif (Universitas Pendidikan Indonesia Kampus Serang, 2022)
During the pandemic, all levels of education, including kindergarten, were required to use technology as a medium for conveying learning messages. This community service aimed to develop the ability of teachers to digital literacy at the Pembina Kalianda State Kindergarten, through education and assistance on the procedures for making digital comics and using the InShot software application. The approach used in this research is gradual training and mentoring. The target subjects in this community service were the teachers of the Pembina Kalianda State Kindergarten. The stages that are passed in this program are preparation, implementation, and assistance. The success of this community service program can be seen through data from interviews, observation, and documentation results. The results showed that by introducing technology users through education and assistance on the procedures for making digital comics and procedures for using the InShot software app, teachers at the Pembina Kalianda State Kindergarten could identify and begin to recognize Digital Literacy and could create digital-based learning media, namely Digital Comics and know how to use them (InShot app Digital Comic). Digital literacy through Digital Comics can attract the attention of teachers to know more about digital-based learning media for AUD and help improve the quality of teachers in providing lessons to their students so that teachers can innovate learning media in kindergarten